Claqitanida Jerux / Nur Anisah Pudding ... [et al.] - Pudding, Nur Anisah; Abd latif, Aqilah; Alan, Clarice Elsa; Harun, Nurul Natasya; Azmi, Nurul 'Aliah Adiba (2021)
Nowadays, various types of food have emerged. There even food that we have never imagined can be created is already being sold in the market today. People nowadays, like to experience new things even in their food. That is why, Claqitanida Enterprise takes this opportunity to bring new foods to the society. Claqitanida Enterprise is a company that has business which is based on the food product industry. The product that is mainly from this company is a pickle that comes from various types of fruits that have its own unique taste which is named as Claqitanida Jerux. With the combination of the fruits and other ingredients to create the pickled. It will give customers a different experience with its unique taste. This goes along with the company mission Expand the market in Malaysia through a smart partnership program between distributors and CLAQITANIDA Jerux. The product is a food that can be enjoyed together with family or friends that come at an affordable price to get. It is very convenient to take it anywhere as it comes with a good packaging. This company is created based on a partnership of five members from which each of them contributed RM 25,000 to the company as a capital that gives them the same share and own crucial position in the company. As the overall capital needed to create the company is RM198,500, the company takes a RM 73,500 loan from RHB Bank to complete the capital after the contribution of each member. Claqitanida Enterprise is located at No. 3, Persiaran Bangi Avenue, Taman Bangi Avenue, 43000 Kajang, Selangor. Which is a very strategic place that consists of the target market for this business like the household, student, workers, and people in the area. This is because, around the location there are University, offices, store, and residential area that can bring the customers to this business. Moreover, this location is in the center from its raw material products that come from various places. This is why the company is chosen to be located there. To be a new company in this food industry, there are of course competitors who are more experienced than this company like ‘Jeruk Madu Pak Ali’ and Jeruk Warisan that were established earlier than Claqitanida Jerux. However, they might have their own weaknesses that provide us something to learn from, so that our business can improve from it. Therefore, we take full attention to their business strategy and operation for us to be better and become more known to customers.